Measurement of Inflammatory Bowel Disease Symptoms: Reliability of an Abbreviated Approach to Data Collection. Issue 10 (October 2015) - Henao, Maria Paula; Bewtra, Meenakshi; Osterman, Mark T.; Aberra, Faten N.; Scott, Frank I.; Lichtenstein, Gary R.; Kraschnewski, Jennifer; Lewis, James D.
Abstract : Background: The Crohn's Disease Activity Index (CDAI) and Mayo score for ulcerative colitis (UC) require symptom recall and/or use of a symptom diary. We examined patients' abilities to recall their symptoms and the day-to-day variability of symptoms. Methods: Patients with UC or CD completed a questionnaire including items from the short CDAI (sCDAI) and the 6-point Mayo score. Patients were randomized to receive a follow-up questionnaire testing recall of the bowel symptom items between 1 and 7 days later. In a second study, patients completed a 7-day electronic diary recording their symptoms. sCDAI and 6-point Mayo scores were computed. Analyses estimated daily variability in the indices and misclassification rates when using fewer than 7 days of data. Results: 100%, 82%, and 90% of CD participants recalled the same disease activity status (i.e., active versus remission) as reported on the initial survey when the follow-up questionnaire was administered 1 to 2, 3 to 5, and 6 to 8 days later, respectively. Compared with using 7 days of data, when using only day 7 data, 3.7% of patients with CD were misclassified as active or inactive. Disease activity was misclassified in 2.8%, 4.9%, and 3.3% of patients by using the last 2, 3, or 4 days, respectively. Results were similar for patients with UC. Conclusions: Patients with CD and UC demonstrated good recall of bowel symptoms for up to 8 days. Additionally, bowel symptoms have relatively little variability within a 7-day period allowing for accurate computation of the sCDAI and 6-point Mayo score using 1 to 3 days of data. Abstract : Article first published online 17 July 2015.Supplemental Digital Content is Available in the Text.